Strategic purchasing and the performance of health-care systems in upper middle income countries: A comparative study - Marziye Hadian; Elaheh Mazaheri; Alireza Jabbari (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Providing financial resources for health services is one of the most important issues in the study of health systems, of which purchasing health services is very essential. The World Health Organization considers strategic purchasing as a key option for improving the performance of health systems. The aim of this study was to identify payment methods for service providers and strategic purchasing strategies in upper middle income countries. MATERIALS AND METHODS: The present study was conducted in the form of a comparative analysis involving comprehensive surveys from 2000 to 2019, by searching keywords for the objective of the study by the search engines through databases including ProQuest, PubMed, Google Scholar, Irandoc, SID, Magiran, Science Direct, Scopus, ISI Web of Science, EBSCO, and Cochrane. RESULTS: A total of five upper middle income countries that used strategic purchases entered the study. Overall, all of them implemented rather similar strategies in terms of strategic purchasing and paying to the providers of the services. CONCLUSION: According to the results of this study, per capita payment for primary health-care and outpatient services seems to be the best option for controlling the costs of the health sector, while the appropriate option for the inpatient department is the most common use of diagnosis-related group. The payment method is to control the costs of the inpatient department.